Peranan Hukum Pidana Terhadap Pemberantasan Tindak Suatu Pidana Narkotika di Indonesia - Gumilar, Lesmana Satria; Pandapotan, Rhenaldo Billy; Hibatulmaqqi, Firas; Hermansyah, Selpina (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2022)
The way law enforcers impose sanctions on perpetrators of narcotics crimes for others, where it is used by perpetrators to meet one's medical needs, because there are so many law enforcers who apply unfairly because they do not see the good side in terms of forgiving reasons and justifying reasons for the perpetrators. , this results in injustice being given to perpetrators where narcotics users for others cannot be categorized as criminals who can threaten the welfare and peace of life in society. Based on this, the author's aim is to analyze the role of law enforcement in providing sanctions against narcotics criminals who use narcotics for others and to analyze the legal protection provided to narcotics criminals who use narcotics for others. In this paper, the writer uses a descriptive analysis method as the research specification, a normative juridical method as an approach method, and the data analysis method used is a qualitative juridical method. The conclusion that the authors get is the role of law enforcement in providing sanctions against narcotics criminals who use narcotics for others to provide sanctions as regulated in Article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics. Legal protection given to narcotics criminals who use narcotics for other people is narcotics users or narcotics abusers who receive treatment through medical rehabilitation or social rehabilitation as regulated in the Formulation of Law Number 35 of 2009 concerning Narcotics.